CP-25 Attenuates the Activation of CD4+ T Cells Stimulated with Immunoglobulin D in Human - Wu, Yu-jing; Chen, Heng-shi; Chen, Wen-sheng; Dong, Jin; Dong, Xiao-jie; Dai, Xing; Huang, Qiong; Wei, Wei (Frontiers in Pharmacology, 2018)
Researchers have shown that the level of Immunoglobulin D (IgD) is often elevated in patients with autoimmune diseases. The possible roles of IgD on the function of human T cell activation are still unclear. Paeoniflorin-6'-O-benzene sulfonate (code: CP-25), the chemistry structural modifications of Paeoniflorin (Pae), was a novel drug of anti-inflammation and immunomodulation. The aims of this study were to determine if human CD4+ T cells could be activated by immunoglobulin D (IgD) via the IgD receptor (IgDR)-Lck pathway and whether the novel compound CP-25 could affect the activation of T cells by regulating Lck. Human CD4+ T cells were purified from peripheral blood mononuclear cells (PBMCs) using microbeads. T cell viability and proliferation were detected by Cell Counting Kit-8 and CFSE Cell Proliferation Kit. Cytokines secreted by T cells were assessed with the Quantibody Human Inflammation Array. The binding affinity and expression of IgDR on T cells were detected by flow cytometry, and protein expression of IgDR, Lck, and P-Lck were analyzed by western blot. IgD was shown to bind to IgDR on CD4+ T cells in a concentration-dependent manner and stimulate the activation and proliferation of these cells by enhancing phosphorylation of the activating tyrosine residue of Lck (Tyr394). CP-25 inhibited the IgD-stimulated activation and proliferation of CD4+ T cells, as well as the production of inflammatory cytokines; it was thus suggested that this process might be related to the downregulation of Lck (Tyr394) phosphorylation. These results demonstrate that IgD amplifies the activation of CD4+ T cells, which could be mediated by Lck phosphorylation. Further, CP-25, via its ability to modulate Lck, is a novel potential therapeutic agent for the treatment of human autoimmune diseases.